Occupational exposure to aflatoxin B1: the case of poultry and swine production - Viegas, Susana (2013)
Although there is an abundance of literature concerning the ingestion of food contaminated with aflatoxin B1 (AFB1), only a small number of studies explore mycotoxin exposure in occupational settings. Taking this into consideration, our study was developed with the intention of elucidating whether there is occupational exposure to AFB1 in Portuguese poultry and swine production facilities. A specific biomarker was used to assess exposure to AFB1. A total of 45 workers (34 from poultry farms; 11 from swine production facilities) participated in this study, providing blood samples. Additionally, a control group (n=30) composed of subjects without any type of contact with agricultural activity was considered. All participants signed a consent form and were provided with the study protocol. Eighteen poultry workers (58.6%) and six workers from the swine production facilities (54.5%) showed detectable levels of AFB1. In the control group, the AFB1 values were all below 1 ng/ml. No significant differences in AFB1 levels in serum between workers from poultry and swine farms were found. Poultry workers, however, showed the highest serum levels and a significant statistical difference between this group and the control group was found. Results suggest that exposure to AFB1 by inhalation occurs in both occupational settings representing an additional risk that needs to be recognised, assessed and prevented.